HEROIC SYMBOLOGY AND ITS HISTORICAL RELEVANCE. A REFLECTION FROM THE TEACHING EXPERIENCE - De la Cruz Villanueva, Carlos (2020)
This essay in general lines is oriented to reflect some classical elements in the heroic symbology, structured in the central monument of the Bolognesi Square of the city of Lima, our intention is to understand and approach the heroic construction as an institutional necessity and archetypal formation in pro of a major civic construct which is the citizen. This brief work identifies under empirical criteria certain elements that will be interconnected during reading, all based on a reflexive experience generated in the teaching experience, which made it possible to roll back research and ideas already raised.